Ngindung ka Waktu, Mibapa ka Jaman: Educational Values in Sundanese Proverbs and Their Implications for Elementary Character Education - Sutrisno, Lucky Taufik; Supriatna, Mamat (Journal of Innovation and Research in Primary Education, 2026)
The Sundanese proverb "Ngindung ka waktu, mibapa ka jaman" embodies educational values balancing tradition preservation with contemporary adaptation, yet remains underexplored as a pedagogical framework for nationalism-based character education in elementary schools. This study examined how educational values embedded in this proverb manifest in Kampung Adat Cireundeu community practices and their implications for elementary education. Employing ethnographic case study design, data were collected through participant observation, semi-structured interviews with traditional leaders (n=2), elementary teachers (n=3), and community members (n=5), and document analysis. Data were analyzed using Miles et al.'s (2014) descriptive analysis framework with methodological triangulation ensuring validity. Five core educational values emerged: love for cultural heritage, social responsibility, unity, adaptive capacity, and independence. These values manifested through concrete practices including cassava-based food self-sufficiency, mutual cooperation (gotong royong), selective technology adoption, and intergenerational knowledge transmission. Comparative analysis revealed philosophical consistency across Indonesian ethnic proverbs. Successful curriculum integration required teacher ethnopedagogical training, curriculum flexibility, and community-school partnerships. The proverb functions as a living pedagogical framework demonstrating that indigenous communities can simultaneously preserve cultural identity while engaging modernity. Findings provide evidence-based guidance for integrating local wisdom into character education curricula, positioning traditional knowledge systems as vital resources for developing culturally grounded, nationally coherent educational frameworks applicable beyond Indonesian contexts.